Family Resilience of MSMEs Traders after Toll Road Operation at Pasar Bengkel: Islamic Family Law Perspective (Mimbar Keadilan, 2023)
This paper aims at seeking how the implementation of family resilience among MSMEs traders after the toll road operation in the view of Islamic family law. This research is empirical legal research with a legal sociology approach. Sources of data were taken from interviews with MSMEs traders and qualitative methods were used to analyze it. The results show that the operation of the Medan-Kualanamu-TebingTinggi toll road affects the economic income of merchant families, the resilience of merchant families is still relatively strong in the view of Islamic family law. This condition was marked by reaching their resilience in terms of aspects of marriage legality, household integrity, fulfillment of rights and obligations, and aspects of conflict management. The efforts made by the families of MSMEs traders after the operation of the Medan-Kualanamu-TebingTinggi toll road maintain family resilience including finding their jobs to cover their lack of income, being open about financial problems and maintaining good communication between family members. Whereas in general the concept of family resilience is still being implemented among MSMEs traders at Pasar Bengkel even though affected by the toll road operation.